Carbon Nanotubes for the Rapid Detection of Intracellular Hydrogen Peroxide and its Application in Bacterial Detection - Hicks, Jacqueline (2019)
The aim of this work is to develop a biosensor capable of detecting bacteria through the specific detection of intracellular hydrogen peroxide. When bacteria interact with host phagocytic immune cells there is a burst of reactive oxygen species known as the respiratory burst. Traditionally this is thought to be a long and extended production of reactive oxygen species. Recent advances however, have shown that the respiratory burst can be more dynamic with a fast and rapid response to bacteria. Conventional techniques for the measurement of reactive oxygen species are limitedin their ability to differentiate between reactive oxygen species and to detect them in a time sensitive manner. In order to fulfil this need for a rapid sensor, an electrochemical nano-biosensor was developed that can interface with cells interacting with the cell cytoplasm and detect hydrogen peroxide in a time and concentration dependent manner. Such a development is a vital first step in the production of a rapid diagnostic device that will aid physicians in correctly treating bacterial infection and will be of particular use in the treatment of sepsis.